2021
DOI: 10.3390/cells10061457
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Restores Impaired Autophagy and Suppresses Inflammation in High Glucose-Treated HK-2 Cells

Abstract: Sodium-glucose cotransporter2 (SGLT2) inhibitors have a reno-protective effect in diabetic kidney disease. However, the detailed mechanism remains unclear. In this study, human proximal tubular cells (HK-2) were cultured in 5 mM glucose and 25 mM mannitol (control), 30 mM glucose (high glucose: HG), or HG and SGLT2 inhibitor, dapagliflozin-containing medium for 48 h. The autophagic flux was decreased, accompanied by the increased phosphorylation of S6 kinase ribosomal protein (p-S6RP) and the reduced phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 60 publications
0
50
0
Order By: Relevance
“…Empagliflozin restored autophagic flux impairment via activating AMPK and suppressing mTOR in H9c2 cells (rat cardiac myoblast) [ 69 ], RAW264.7 and THP-1 cells (macrophage cell lines) [ 70 ]. Our previous study also indicated that dapagliflozin had similar effects on autophagy restoration via AMPK/mTOR signaling in high-glucose-treated proximal tubular cells [ 71 ].…”
Section: Mechanisms Of Sglt2 Inhibitors Against Atherosclerosismentioning
confidence: 98%
“…Empagliflozin restored autophagic flux impairment via activating AMPK and suppressing mTOR in H9c2 cells (rat cardiac myoblast) [ 69 ], RAW264.7 and THP-1 cells (macrophage cell lines) [ 70 ]. Our previous study also indicated that dapagliflozin had similar effects on autophagy restoration via AMPK/mTOR signaling in high-glucose-treated proximal tubular cells [ 71 ].…”
Section: Mechanisms Of Sglt2 Inhibitors Against Atherosclerosismentioning
confidence: 98%
“…By blocking sodium glucose co-transport and reducing blood glucose levels, SGLT2i demonstrate improved renal and cardiovascular outcomes in patients with T2DM and diabetic nephropathy [ 92 , 93 , 94 ]. Whilst initial protection is thought to stem from a decrease in glomerular hyperfiltration, several studies demonstrate that SGLT2i confer protection via suppression of inflammation and fibrosis, albeit the widespread mechanisms remain to be fully elucidated [ 95 , 96 , 97 ]. However, with prescription targeted to individuals with T2DM as opposed to T1DM and potential side effects that include ketoacidosis [ 98 ], increased risk of amputation [ 99 ], and increased genitourinary tract infection [ 100 ], SGLT2i are not a one size fits all.…”
Section: Targeting Inflammation In Microvascular Complications Of Diabetesmentioning
confidence: 99%
“…Since transcription of the genes that encode proinflammatory cytokines is controlled by the master transcription factor nuclear factor κB (NF-κB), the authors tested the hypothesis that dapagliflozin may interact with this transcription factor. Indeed, they found that the p65 subunit of NF-κB is suppressed in proximal tubular cells exposed to high-glucose medium with dapagliflozin and that such a suppression is secondary to AMPK activation [ 24 ]. In summary, these authors were able to demonstrate the complex action of SGLT2i on several mechanisms involved in the control of autophagy and inflammation, and that the multilevel derangement of these mechanisms triggered by high glucose can be restored at several points by using dapagliflozin.…”
Section: Sglt2i As Antioxidative and Anti-inflammatory Agents In Dkd And Other Models Of Kidney Injurymentioning
confidence: 99%
“…Decrease synthesis of proinflammatory cytokines: interleukin 1β (IL1β), interleukin 6 (IL6) and tumor necrosis factor α (TNFα) through inhibition of NF-κB [ 24 , 25 , 35 , 37 , 66 , 73 , 82 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation